2013
DOI: 10.1093/jat/bks092
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Ractopamine Residues in Hair and Ocular Tissues of Animals during and after Treatment

Abstract: The aim of the present study was to assess the accumulation of ractopamine residues in the hair and ocular tissues of guinea pigs during repeated ractopamine administration and after treatment. The experiment was conducted in 38 guinea pigs (30 treated and eight controls). Treated animals were orally administered ractopamine hydrochloride in a dose of 3.5 mg/kg body mass per day using probes for seven consecutive days. Ractopamine concentration was determined in hair during the treatment (Days 1, 3 and 7) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…Ractopamine residues in plasma and urine of cattle (mean ± SE, n = 3) fed 0.67 mg/kg body weight of ractopamine for 28 days not surprising to find high ractopamine residue concentrations in lung tissues because ractopamine is a β-agonist in the same category as salbutamol, which is used for the treatment of human asthma. The three tissues with the greatest concentration of residual ractopamine in this study included the eyes, which was inconsistent with previously reported results (15,16). Smith et al (16) demonstrated that the propensity for binding of ractopamine to melanin is weaker than that of clenbuterol and ractopamine was undetectable in whole-eye homogenates from cattle dosed with 0.9 mg/kg per day for 7 days.…”
Section: Residues Of Ractopamine In Plasma Urine and Tissuescontrasting
confidence: 99%
See 1 more Smart Citation
“…Ractopamine residues in plasma and urine of cattle (mean ± SE, n = 3) fed 0.67 mg/kg body weight of ractopamine for 28 days not surprising to find high ractopamine residue concentrations in lung tissues because ractopamine is a β-agonist in the same category as salbutamol, which is used for the treatment of human asthma. The three tissues with the greatest concentration of residual ractopamine in this study included the eyes, which was inconsistent with previously reported results (15,16). Smith et al (16) demonstrated that the propensity for binding of ractopamine to melanin is weaker than that of clenbuterol and ractopamine was undetectable in whole-eye homogenates from cattle dosed with 0.9 mg/kg per day for 7 days.…”
Section: Residues Of Ractopamine In Plasma Urine and Tissuescontrasting
confidence: 99%
“…Smith et al (16) demonstrated that the propensity for binding of ractopamine to melanin is weaker than that of clenbuterol and ractopamine was undetectable in whole-eye homogenates from cattle dosed with 0.9 mg/kg per day for 7 days. Likewise, Pleadin et al (15) also reported low ractopamine residue concentrations in the ocular tissues of guinea pigs (0.34-1.20 ng/g) following administration of 3.5 mg/kg body mass of ractopamine for 7 days. However, in the present study, ractopamine residue levels were comparatively high in eye tissues.…”
Section: Residues Of Ractopamine In Plasma Urine and Tissuesmentioning
confidence: 89%
“…Overall. It is clear that the risk of exposure to ractopamine residues is greater in goat tissues than in sheep tissues (4,25). The residues in liver and became undetectable after 95 h in goat and 82 h in the sheep, similar to delays reported for clenbuterol, a β 2 -agonist, in goat tissues (8,26).…”
Section: Discussionsupporting
confidence: 65%
“…Introduction β-Agonists exhibit short-acting effects and long-acting effects and are frequently used to promote growth in livestock, but problems arise when the residues of such veterinary drugs have the potential to influence human health after being consumed in animal products (1)(2)(3)(4)(5). Evaluation of β-agonist as a veterinary drug is a new concept to implement the principle using medicines for veterinarian by motto: logic and responsibility.…”
Section: ‫تقييم‬ ‫طرح‬ ‫مدة‬ ‫واألغنام‬ ‫الماعز‬ ‫في‬ ‫الراكتوبامين‬ mentioning
confidence: 99%
“…Some investigations have used R on guinea pigs (cavies) and other rodents. In the specific case of the guinea pig, which is a laboratory animal model, metabolites of R were traced and measured in different concentrations and in different tissues, such as skeletal muscle (11)(12)(13)(14). The production of this species for human consumption has historically occurred in countries on the American continent, including Andean countries such as Peru and Ecuador (15,16); currently, it is also found in other parts of the world, such as some regions of Cameroon (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%